The impact of frequency of alenternating electric field on seed germination and growth of cereal crops - Solovei, I.; Semenova, N.; Haidukevych, S. (Energy and Automation, 2025)
The challenge with improving cereal crop yields while reducing production costs is still significant today. The similarity within seeds is one of main indicators for assessing the quality of the plating material; others also involve purity, planting compatibility, and germination. Alternating electric fields is a potential method for influencing agricultural crop seeds. This study explores the effect of alternating electric fields at ranging frequencies on crops with the goal of increasing seed germination and plant development. The research focused on the processing of winter wheat.The purpose of the research is to determine the influence of the frequency of an alternating electric field on the germination process and growth of grain seeds to ensure an effective and energy-saving method of pre-sowing treatment of planting material.Wheat seeds were processed with an alternating electric field in a laboratory environment while applying a specifically constructed system that included an industrial alternating voltage generator, the PM 5106 LF Generator, which allows for necessary voltage frequency modifications. At the output ports of the generator, chambers were constructed for the grains to later be processed with an alternating electric field.We show the wheat processing with the possibility for further practical utilization of an alternating electric field with variable frequencies in electrical structure for winter wheat processing at the highest efficiency levels. These alternating electric field frequencies have proven to display positive effects on crop yield and quality.The presented electro technology of processing crops, considering the variable frequencies in alternating electric fields, seems to favorably differ from the already existing ones. This allows for better indicators of similarity and development of the plants and consequently increases the wheat crop yield.Key words: frequency, alternating electric field, energy consumption, productivity, power